Clinical characteristics, treatment patterns, and survival in mantle cell lymphoma: a real-world cohort - de la Hoz, Cesar; Hurtado-Otiz, Alexandra; Licht-Ardila, Maricel; Cantillo, Ana; Silva, Andrea; Herrera, Leidy; Alvarez, Paola; Vega Jiménez, Olga Daniela; Fonseca, Jaiver; Mendoza-Monsalve, Alejandra; Avila, Jhon Alexander; Manrique-Hernández, Edgar Fabián (Frontiers in Oncology, 2026)
IntroductionMantle cell lymphoma is a rare, typically aggressive B-cell non-Hodgkin lymphoma that often presents at an advanced stage and carries substantial long-term mortality despite therapeutic advances. Multiple clinical, biological, and treatment-related factors may influence survival in these patients.ObjectiveTo describe the clinical characteristics, treatment patterns, and overall survival of patients with mantle cell lymphoma at a high-complexity referral center in a middle-income country.MethodsThis retrospective cohort included adult patients diagnosed and managed at a high-complexity referral center in Colombia between January 2016 and October 2025. Overall survival was the primary outcome. Survival estimates were obtained using Kaplan–Meier curves and compared with log-rank tests.ResultsA total of 41 patients were included, with 43.9% aged <65 years. Baseline clinical, laboratory, immunophenotypic, and cytological characteristics were similar across age groups, with most patients presenting with advanced disease, including Ann Arbor stage IV (66.7% vs. 72.3%) and high-risk MIPI classification (88.9% vs. 100%). First-line treatment differed by age, with younger patients more frequently receiving Nordic regimens and older patients receiving R-bendamustine; however, response rates were comparable. Overall survival did not differ significantly by sex, age group, Ann Arbor stage, or LDH levels. In contrast, MIPI category significantly predicted survival (log-rank p=0.017).ConclusionThis real-world cohort describes patients with mantle cell lymphoma presenting predominantly with advanced-stage, high-risk disease. Treatment approaches differed by age, with comparable overall responses across groups. The findings suggest that prognostic indices and functional status assessment may aid outcome evaluation in routine practice.